Absence of Plasmodium inui and Plasmodium cynomolgi, but detection of Plasmodium knowlesi and Plasmodium vivax infections in asymptomatic humans in the Betong division of Sarawak, Malaysian Borneo - Siner, Angela (Malar J, 2017)
BACKGROUND: Plasmodium knowlesi, a simian malaria parasite, has become the main cause of malaria in Sarawak, Malaysian Borneo. Epidemiological data on malaria for Sarawak has been derived solely from hospitalized patients, and more accurate epidemiological data on malaria is necessary. Therefore, a longitudinal study of communities affected by knowlesi malaria was undertaken. METHODS: A total of 3002 blood samples on filter paper were collected from 555 inhabitants of 8 longhouses with recently reported knowlesi malaria cases in the Betong Division of Sarawak, Malaysian Borneo. Each longhouse was visited bimonthly for a total of 10 times during a 21-month study period (Jan 2014–Oct 2015). DNA extracted from blood spots were examined by a nested PCR assay for Plasmodium and positive samples were then examined by nested PCR assays for Plasmodium falciparum, Plasmodium vivax, Plasmodium malariae, Plasmodium ovale, Plasmodium knowlesi, Plasmodium cynomolgi and Plasmodium inui. Blood films of samples positive by PCR were also examined by microscopy. RESULTS: Genus-specific PCR assay detected Plasmodium DNA in 9 out of 3002 samples. Species-specific PCR identified 7 P. knowlesi and one P. vivax. Malaria parasites were observed in 5 thick blood films of the PCR positive samples. No parasites were observed in blood films from one knowlesi-, one vivax- and the genus-positive samples. Only one of 7 P. knowlesi-infected individual was febrile and had sought medical treatment at Betong Hospital the day after sampling. The 6 knowlesi-, one vivax- and one Plasmodium-infected individuals were afebrile and did not seek any medical treatment. CONCLUSIONS: Asymptomatic human P. knowlesi and P. vivax malaria infections, but not P. cynomolgi and P. inui infections, are occurring within communities affected with malaria.